Understanding health behaviors, weight perceptions, and body appreciation of young adult women engaged in the body positivity movement - Rupp, Kristie; McCoy, Stephanie M. (Women's Health Issues, 2023)
Background The body positivity movement on social media is thought to foster body appreciation, but pervasive societal concern persists about the body positivity movement and the body image, health behaviors, and “normalization of obesity” of young adult women. Purpose This study explored the relationship between engagement in the body positivity movement on social media and weight status, body appreciation, body dissatisfaction, and the health behaviors of intuitive eating and physical activity in young adult women (18–35 years). Methods Participants (N = 521; ∼64% engaged in body positivity content on social media) were recruited using Qualtrics online panels for this cross-sectional survey during February 2021. Outcomes included weight status, weight consideration, weight perception, body appreciation, body dissatisfaction, physical activity, and intuitive eating. Logistic and linear regression models adjusted for age, race, ethnicity, education level, and household income were used to assess the association between engagement in the body positivity movement and specified outcomes. Results Engagement in body positivity content was associated with greater body dissatisfaction (β = 2.33, t(519) = 2.90 p = .017), body appreciation (β = 0.26, t(519) = 2.90 p = .004), and greater likelihood of reporting high amounts of physical activity (odds ratio = 2.28; p < .05) relative to nonengaged peers; these associations remained significant after further adjustment for weight status. Body positivity was not associated with weight status, weight perception, or intuitive eating. Conclusions Engagement in the body positivity movement is associated with higher body dissatisfaction and body appreciation in young adult women, which suggests they may be drawn to and engage in the body positivity movement as a protective or coping mechanism for body dissatisfaction.
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms; peer-reviewed